1958
DOI: 10.1103/physrev.112.1950
|View full text |Cite
|
Sign up to set email alerts
|

Two New Promethium Isotopes; Cross Sections of Some Samarium Isotopes for 14.8-Mev Neutrons

Abstract: When highly enriched samples of Sm 152 and Sm 154 are irradiated with 14.8-Mev neutrons, activities having half-lives of 6.5±0.5 min and 2.5±0.5 min are observed. On the basis of yields and cross-bombardments, these are assigned to new isotopes Pm 152 and Pm 154 , respectively. Cross-section measurements at 14.8 Mev for (n,2n), (n,p), and (n,a) reactions of samarium are reported, the experimental values being as follows: Sm 144 (rc», 1200=b300 mb; Sm 154 (ra», 1500±300 mb; Sm™(n } p), 3.7±0.2 mb; Sm™(n,p), 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Therefore, we have investigated the/?--decay of 152pm and have found [17] three isomers with half-lives of 4.2+0.2rain, 7.5+0.2min and 15.0+ 1.0min. Previous studies [18][19][20][21][22][23][24] on the decay of ~SZPm have reported only half-lives and a few ~,-rays, but discrepancies even existed in the half-lives. In the course of our investigations Daniels and Hoffman [25] have independently discovered three isomers of 152pm and have investigated their decay in some detail.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, we have investigated the/?--decay of 152pm and have found [17] three isomers with half-lives of 4.2+0.2rain, 7.5+0.2min and 15.0+ 1.0min. Previous studies [18][19][20][21][22][23][24] on the decay of ~SZPm have reported only half-lives and a few ~,-rays, but discrepancies even existed in the half-lives. In the course of our investigations Daniels and Hoffman [25] have independently discovered three isomers of 152pm and have investigated their decay in some detail.…”
Section: Introductionmentioning
confidence: 89%
“…152 Pm was discovered by Wille and Fink in the 1958 paper "Two new promethium isotopes; cross sections of some samarium isotopes for 14.8-MeV neutrons" [178]. Enriched 152 Sm 2 O 3 was bombarded with 14.8-MeV neutrons produced in the reaction 3 H(d,n) 4 He from the Arkansas Cockroft-Walton accelerator.…”
Section: Pmmentioning
confidence: 99%